Does a jammer-type racing swimsuit improve sprint performance during maximal front-crawl swimming? - Moriyama, S.-I.; Mankyu, H.; Tsunokawa, T.; Kurono, T.; Mizukoshi, H.; Ogita, F. (Sports Biomechanics, 2021)
We investigated the effects of jammer-type racing swimsuits (RS) on swimming performance during arm-stroke-only (pull) and whole-body stroke (swim) in 25-m front-crawl with maximal effort. Twelve well-trained male collegiate swimmers wore RS and a conventional swimsuit (CS) and performed three tests: pull, swim, and pull using the system to measure active drag (MAD pull). Swimming velocity and intra-abdominal pressure (IAP) were determined in all tests. Stroke indices during pull and swim and drag-swimming velocity relationship and maximum propulsive power during MAD pull were also determined. Swimming velocities during pull and swim while wearing an RS (1.59±0.13 and 1.77±0.09 m/s, respectively) were significantly higher than those wearing a CS (1.57±0.14 and 1.74±0.08 m/s, respectively). Stroke length during pull and swim was significantly greater while wearing an RS (1.68±0.12 and 1.83±0.13 m, respectively) than wearing a CS (1.63±0.10 and 1.81±0.13 m, respectively). However, no significant differences were confirmed between the other variables in all tests. In conclusion, swimming performance is improved when wearing an RS compared with a CS.